BOOK REVIEW: Diana Mărgărit, Ciprian Jeler (eds.). “Seriozitatea jocului. O abordare multidisciplinară a ludicului”, Editura Universității ‟Alexandru Ioan Cuza”, Iași, 2021, 224 p. - Radu SIMION (Studia Universitatis Babeș-Bolyai. Philosophia, 2022)
“Seriozitatea jocului. O abordare multidisciplinară a ludicului” ("The seriousness of playing. A multidisciplinary approach to playfulness"), coordinated by Diana Mărgărit and Ciprian Jeler, was published in 2021 at the “Alexandru Ioan Cuza” University Publishing House, introducing the topic of game, as seen from the perspective of ten original contributions of researchers and authors dedicated to this vast topic. Playing, an activity that does not seem to raise major epistemic issues, comes out unfolding its multiple dimensions such as semantic, aesthetic, historical, social, anthropological or ontological relevance. As a philosopher interested in topics that encompass a wide range of extended applicability disciplines, the subject of play seems to me as much fascinating and spectacular as it is peculiar, mysterious, enticing.